Risk Analysis in Human Resource Management: The Role of Ethics and Control Mechanisms in Organizational Performance - Ginna Novarianti Dwi Putri Pramesti (Worldwide Research Publishing, 2025)
This research explores the role of ethics and control mechanisms in human resource management (HRM) and their impact on organizational performance. The problem studied is how organizations face challenges in managing HR risks related to low compliance with ethics and weaknesses of internal control mechanisms that can reduce organizational performance. This research aims to develop and test an integrated model that connects organizational ethics, control mechanisms, and human resource management (HRM) risk management to improve organizational performance. Using a mixed-methods approach, this study combined quantitative surveys and qualitative interviews with HR professionals in 10 organizations. The findings suggest that a strong organizational ethical culture has a positive effect on the effectiveness of internal control mechanisms, which in turn improves the risk management capabilities of human resource management (HRM). This ability directly contributes to the improvement of organizational performance. The study also identified that control mechanisms mediate the relationship between ethics and human resource management (HRM) risk management. The results show that integrating ethics into the human resource management (HRM) risk management framework is critical for organizational resilience and performance. This research contribution offers a comprehensive model for HR managers to integrate ethical practices and control systems, leading to better risk mitigation strategies and more optimal organizational outcomes. Implications for practice include strengthening ethical culture, improving control mechanisms, and implementing proactive human resource management (HRM) risk management strategies. The limitations of this study include the narrow scope of the organization, and further research can explore applications in a wider industry.